2019
DOI: 10.3390/pr7070474
|View full text |Cite
|
Sign up to set email alerts
|

Research on Green Management Effect Evaluation of Power Generation Enterprises in China Based on Dynamic Hesitation and Improved Extreme Learning Machine

Abstract: Carbon emissions and environmental protection issues have become the pressure from the international community during the current transitional stage of China’s energy transformation. China has set a macro carbon emission target, which will reduce carbon emissions per unit of Gross Domestic Product (GDP) by 40% in 2020 and 60–65% in 2030 than that in 2005. To achieve the emission reduction target, the industrial structure must be adjusted and upgraded. Furthermore, it must start from a high-pollution and high-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…S. Mojrian [61] used the radial-base-function (RBF) kernel of the Extreme Learning Machine (ELM) classification model with the Online Support Vector Machine and other baseline models. The Extreme Learning Machine with RBF kernel performs well under the evaluation metrics of accuracy, precision, mindfulness, and specificity; meanwhile, the algorithm of RBF-ELM proposed by Y. Qin [62] is validated on a lowcarbon engineering problem, which further illustrates the computational classification advantages brought by RBF in mapping input vectors to a high-dimensional special space. The RBF formulation is shown in Equation ( 5), where σ is the kernel parameter:…”
Section: Establishment Of the Sunflower Origin Identification Model 2...mentioning
confidence: 92%
“…S. Mojrian [61] used the radial-base-function (RBF) kernel of the Extreme Learning Machine (ELM) classification model with the Online Support Vector Machine and other baseline models. The Extreme Learning Machine with RBF kernel performs well under the evaluation metrics of accuracy, precision, mindfulness, and specificity; meanwhile, the algorithm of RBF-ELM proposed by Y. Qin [62] is validated on a lowcarbon engineering problem, which further illustrates the computational classification advantages brought by RBF in mapping input vectors to a high-dimensional special space. The RBF formulation is shown in Equation ( 5), where σ is the kernel parameter:…”
Section: Establishment Of the Sunflower Origin Identification Model 2...mentioning
confidence: 92%
“…A comprehensive set of manufacturer evaluation criteria in utilizing AHP was constructed by Hossein [14], aiming to allocate different weight proportions to eight evaluation indicators. Qin [15], who conducted research on the green operation benefits of power generation enterprises, proposed an intuitionistic fuzzy comprehensive analytic hierarchy process based on improved dynamic hesitation degree (D-IFAHP) and an improved extreme learning machine algorithm optimized by the RBF (radial basis function) kernel function (RELM), which simplifies the manufacturing evaluation process. Another expert scoring method is the Delphi method, which has been mentioned in the context of smart shipping [16] and smart health [17], but has not been applied to smart manufacturer evaluation.…”
Section: State Of the Art Of Smart Manufacturer Evaluationmentioning
confidence: 99%
“…Experiment results from UCI data revealed that their method was better in generalization compared to original ELM. Qin and Li [139] applied ELM to evaluate the green management in power generation enterprises in China. Firstly, an evaluation indicator system for low carbon sustainability was created by an improved dynamic hesitation degree.…”
Section: Chemistry Applicationmentioning
confidence: 99%